A Review of Intracranial Hemorrhage Detection by Deep Learning Techniques - M. Raja Suguna, A. Kalaivani (International Journal of Advanced Science and Technology, 2020)
Intracranial Hemorrhage is a traumatic brain injury (ICH). ICH should be accurately diagnosed otherwise it leads to a death and disabilities to the humans. It is Clinically diagnosed by Computer Tomographic Images (CT) Images or by using Magnetic Resonance Images consulted by Doctors assisted by radiologists. Computer Aided Automatic Diagnosing (CAD) Tools helpful in accurately localize the Hemorrhage areas in the brain. These CAD Tools are designed by image processing Algorithms. In this paper, a detailed review on Deep learning Algorithms used in the detection of Intracranial Hemorrhage in literature are studied.